PENGARUH PENGELUARAN PER KAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PULAU SUMATERA PERIODE 2018-2021 - Al Akbar; Andri Irawan; Agung Dwi Wijaya (Ekonomika, 2023)
This research entitled The Influence of Per capita Expenditure on the Human Development Index on the Island of Sumatra in 2018-2021. The purpose of this study was to determine whether there was an influence of per capita expenditure on the human development index on the island of Sumatra. This research was conducted on the island of Sumatra. This research method was panel data analysis method. The data used in the form of secondary data. The data source for this research was obtained from the Indonesian Central Statistics Agency (BPS) in 2018-2021. The results of this study were obtained using the panel data analysis method to show that the variable per capita expenditure had a significant influence on the human development index on the island of Sumatra. The result of the coefficient of determination (R2) said that only 32.25% while the remaining 67.75% was influenced or explained by other variables not included in the research model such as economic growth, consumption expenditure and inflation